THE ROLE OF INNOVATIVE CITIZENSHIP BEHAVIOR IN IMPROVING EMPLOYEE PERFORMANCE - Fitrio, Tomy; Indra Saputra, Raja Marwan; Dewi, Puspa; Astarina, Ivalaina (Jurnal Aplikasi Manajemen, 2022)
This paper takes the dynamic capabilities (DCs) theory as a theoretical perspective to investigate the role of innovative citizenship behavior as a mediation model in the effect of organizational commitment and culture on the performance of Bank X employees in Indonesia empirically. The data were collected from 340 people and processed using Structural Equation Modeling (SEM). The study proposed innovative citizenship behavior as a strategy for improving employee performance based on the concept of organizational citizenship and innovative behavior. The results showed that organizational commitment and culture mediated by innovative citizenship behavior improve employee performance. That supports the hypothesis of the importance of innovative citizenship behavior in enhancing employee performance. These results strengthen the theory of dynamic capabilities (DCs), which states that reconfiguring internal drive, in this case, employees increases the company's competitive advantage in a dynamic environment.